Chromeno naphthyridines based heterocyclic compounds as novel acidizing corrosion inhibitors: Experimental, surface and computational study - Salman M.; Ansari K.R.; Srivastava V.; Chauhan D.S.; Haque J.; Quraishi M.A. (My University, 2025)
In the present work three chromeno naphthyridine derivatives (CNs) have been synthesized using one pot multicomponent reaction of 2, 4-hydroxyacetophenone, aromatic aldehydes and malononitrile in water using silica gel as a catalyst. The simulated LD50 values for the synthesized compounds are 340 mg/kg (CN-1), 1500 mg/kg (CN-2) and 800 mg/kg (CN-3) which suggest their non-toxic and eco-friendly nature The performance all the three compounds as corrosion inhibitors in 15% HCl on N80 has been analyzed via weight loss, electrochemical, surface characterization, and density functional theory (DFT) methods. Chromeno naphthyridine (CN-1) shows maximum inhibition efficiency of 98.3% at only 300 mg/L. The measurement of EIS reveals the process of inhibition of corrosion is governed by control of charge transfer. The mixed nature of CNs adsorption is suggested by results of PDP. Langmuir model of adsorption shows the perfect fitting. Adsorption of CNs onto the metal surface was supported by FTIR, AFM, and UV–vis. Computational modelling using DFT data reveals that corrosion inhibition takes place by adsorption of both neutral and protonated forms on steel surface. Molecular dynamic simulation (MDS) suggests the parallel adsorption of CNs molecules both in neutral and protonated forms. © 2020 Elsevier B.V.